Indonesia's leadership transition : will Jakarta's foreign policy change? - Awidya Santikajaya (2014)
The forthcoming leadership transition in Indonesia will not result in radical foreign policy change. However, Indonesia is likely to diversify its foreign policy choices by promoting its emerging middle power status. This article continues a series on this year’s national elections.